Exploring computer simulation to assess counseling skills amongst pharmacy undergraduates - Pereira, D. V. (2015)
Pharmacists are considered medicine specialists referring to minor ailment treatment and self-medication counseling. Although increasingly important in pharmacy training, there are limited initiatives comprising the use of computer simulation. The study objective was to explore minor ailment counseling skills from Portuguese pharmacy undergraduates through an experimental virtual patient methodology. This study followed a prospective cross-sectional design, with all students from Portuguese higher education pharmacy institutions being invited to use a virtual interactive simulator for over-the-counter medication advice giving. Data analysis comprised descriptive and regression statistics. Seven hundred and seven students replied from eight Portuguese pharmacy schools. Older students (≥22 years) and those with previous pharmacy practice experience presented significantly better overall counseling performance. Regression results confirmed therapeutic counseling success to be a function of years of education, with a significant better performance for 4th, 5th and internship students, while all cohorts presented equivalent simulator acceptance. As a conclusion, one can say that pharmacy degrees in Portugal seem to address counseling training needs of future pharmacists. Results suggested advantages in advice-giving skills if contact with practice occurs during undergraduate education. Knowing the present relevance of electronic means in education, ways of providing computer standardized training and practice assessment should be implemented and consistently used.